An unified model for dislocations interacting with complex-shape voids in irradiated metals. (1st November 2020) - Chen, Yang; Liu, Yanbin; Fang, Qihong; Li, Jia; Liu, Yong; Liaw, Peter K
Highlights: Interaction between dislocation and complex-shape void is studied. A analytical formula is developed to predict the CRSS for arbitrary shape void. The flat polygonal void contributes to the high CRSS. The effect of ratio between void spacing and size for CRSS is studied. A new bypass mechanism is proposed in complex-polygonal void. Abstract: The irradiation damage-induced voids can hinder dislocation glide, and thereby change the mechanical properties in the nuclear materials. However, the detailed process of the dislocation interacting with complex-shape void is not revealed well. Here, we study systematically the interaction between an edge dislocation and a polygonal void with different initial geometries in the irradiated metals by dislocation dynamics simulations, in terms of the critical resolved shear stress (CRSS). The polygonal-void shape and the ratio between the void size and spacing on CRSS are investigated, to explore the void-shape-dependent strengthening behavior. The results show that the relationship between the CRSS and the harmonic mean of the void size and spacing is consistent with the previous work obtained by molecular dynamics simulations during the dislocation bypassing the circular void process. At a given void size, a larger void spacing results in a higher CRSS, owing to the needed external shear force required for dislocation bypassing. To clarify the irradiation hardening contributed by the void, we propose an analytical formula considering an arbitrary void-shape geometry at various irradiation doses and temperatures, and predict CRSS for the dislocation interacting with the arbitrary void shape. In addition, compared to the circular void, the flat polygonal void contributes to a higher CRSS due to the serious degree of dislocation bow-outs induced by the polygonal void, yielding new strategy to increase the service life and avoid failure. The current result enables an in-depth understanding of a void-shape-dependent strengthening mechanism at nanoscale in irradiated materials, and further guides the design of radiation-tolerant materials by tuning irradiation-void geometry. Graphical abstract: Image, graphical abstract